Homocysteine induces mitochondrial dysfunction involving the crosstalk between oxidative stress and mitochondrial pSTAT3 in rat ischemic brain - Shuang Chen (Nature Portfolio, 2017)
Abstract Homocysteine (Hcy) has been shown to have a neurotoxic effect on ischemic brain cells; however, the underlying mechanisms remain incompletely understood. Here, we examined whether Hcy treatment influences mitochondria injury, oxidative stress, and mitochondrial STAT3 (mitoStat3) expression in rat ischemic brain. Our results demonstrated that Hcy treatment aggravated the damage of mitochondrial ultrastructure in the brain cortex and the dentate gyrus region of the hippocampus after focal cerebral ischemia. An elevated Hcy level was also accompanied by the significant inhibition of mitochondrial complex I–III enzymatic activities in addition to an increase in cytochrome c release. 8-Hydroxy-2′-deoxyguanosine (8-OHdG) content and mitoStat3 protein phosphorylation level were increased in Hcy-treated animals, whereas AG490, a Jak2 inhibitor, inhibited mitoStat3 phosphorylation as well as 8-OHdG levels induced by Hcy. In vitro studies revealed that Hcy also markedly increased reactive oxygen species (ROS) and mitoStat3 levels. In addition, the inhibition of pSTAT3 reduced Hcy-mediated increase in ROS levels, whereas quenching ROS using the ROS inhibitor glutathione ethyl ester inhibited Hcy-mediated pSTAT3 overactivation in Neuro2a cells. These findings suggest that the development of therapies that interfere with the ROS/pSTAT3 pathway may be helpful for treating cerebral infarction-related diseases associated with Hcy.